COVID-19, inclusion and workforce diversity in the cultural economy: what now, what next?. Issue 3 (26th May 2020) - Eikhof, Doris Ruth
ABSTRACT: The impact of the COVID-19 pandemic on the cultural economy poses a significant threat to inclusion and workforce diversity. This article combines pre-COVID-19 research with emerging industry and policy evidence to identify where key impacts on inclusive practice and, consequently, workforce participation and advancement in the cultural economy are likely to occur. The article demonstrates how considering the cultural economy's typical business models and resultant work and employment practices allows understanding that the inclusion and diversity impacts of the COVID-19 pandemic will be driven by more than workers' differing abilities to buffer short-term income insecurity. The article highlights four areas relevant to inclusion and workforce diversity that research and policy responses to COVID-19 should attend to in revising existing and designing new responses to the COVID-19 pandemic.